Prepare the patient for future challenges when facing hemodialysis: nurses' experiences - Anna Sturesson; Kristina Ziegert (International Journal of Qualitative Studies on Health & Well-Being, 2014)
Chronic kidney disease is a major health problem due to the significant financial burden for the healthcare system and likewise for the patient who needs the treatment. The patient's whole life situation is turned upside down with chronic kidney disease when they are confronted with the forced change to start treatment with hemodialysis. Patients with chronic kidney disease experience a lack of adequate emotional support from nurses during the transition to hemodialysis. The purpose of this study was to explore nurses’ experiences of giving support to patients during the transition to hospital-bound hemodialysis. The study had a qualitative descriptive design with a content analysis approach; eight nurses from four hospitals in the south of Sweden participated. The results showed that the nurses gave threshold support with an openness and awareness of the patient's individual needs during the transition, except that there seemed to be a lack of knowledge and ability to provide emotional support. Patient support during the transition could therefore be absent. Education, at local and national levels, is needed for the nurse to be able to give professional emotional support. Further research is also desired in order to provide nurses with the tools they need to give emotional support, which is of utmost importance.